Survey methods in social investigation - Moser, Claus Adolf; G. Kalton (London, United Kingdom : Heinemann Educational Books Ltd, 1972)
The net effect is to make a few parts of the book harder. This reflects the fact that techniques have become more rigorous and is in line with the teaching of the subject; courses on survey methods in universities and technical colleges have become notably more sophisticated in a technical sense. We have, however, kept the harder sections down to an absolute minimum and only a small part of the book is above the technical level of the First Edition.
Chapter 1. The nature of social surveys, and some examples -- Chapter 2. The planning of social surveys -- Chapter 3. The coverage of surveys -- Chapter 4. Basic ideas of sampling -- Chapter 5. Types of sample design -- Chapter 6. Further types of sample design -- Chapter 7. Other aspect of sampling -- Chapter 8. An example of a national random sample design -- Chapter 9. Experiments and investigations -- Chapter 10. Methods of collecting the information I -- Chapter 11. Methods of collecting the information II -- Chapter 12. Methods of collecting the information III -- Chapter 13. Questionnaires -- Chapter 14. Scaling methods -- Chapter 15. Response errors -- Chapter 16. Processing of the data -- Chapter 17. Analysis, interpretation and presentation -- Chapter 18. Concluding remarks -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: SOCIAL INVESTIGATION